Dimensions and Projections of Economic Growth in Bulgaria, the European Union and the World - Pirimova, Vera (Research Papers, 2025)
The main goal of the analysis in the article is to reveal and justify the relationship between basic and alternative concepts of growth, on the one hand, and the possibilities for applying different methods of analysis and measures of economic growth, on the other hand. The necessity and the possibility of applying some short-term mathematical-statistical methods to the long-term periods and dynamics of growth are proved. In this regard, the dynamics of GDP in Bulgaria, the European Union and the world in the period 1980 – 2020 were studied. It is concluded that short-term methods (for example chain rates) complement summaries of the application of long-term methods (basic rates), specific features are derived and specified, knowledge of the nature of macroeconomic dynamics is enriched. The report applies the methods of analysis and synthesis, mathematical and statistical methods, as well as methods of descriptive analysis.
Keywords: Growth indicators; Chain and base rates of GDP; Economic growth in Bulgaria; The EU and the world; Economic growth